An analytical review on probable anti-parkinsonian effect of modafinil - Mehdi Farhoudi (Journal of Analytical Research in Clinical Medicine, 2013)
Restoring dopamine levels in Parkinson's disese (PD) has been considered as the main symptomatic therapy. In this strategy, long-term administration of L-DOPA results in motor impairments. This necessitates novel approaches in that PD is tackled with lower deleterious side effects. . Modafinil is a wake promoting agent clinically used for treatment of excessive day time sleeping. This medication increases dopamine levels and decreases oxidative stress and can thus exert anti-parkinsonian effect. Therefore, this review will give an account of the probable anti-parkinsonian mechanisms of modafinil.